Secondary cytomegalovirus infections: How much do we still not know? Comparison of children with symptomatic congenital cytomegalovirus born to mothers with primary and secondary infection - Scaramuzzino, Fabiola; Di Pastena, Michela; Chiurchiu, Sara; Romani, Lorenza; De Luca, Maia; Lucignani, Giulia; Amodio, Donato; Seccia, Annalisa; Marsella, Pasquale; Grimaldi Capitello, Teresa; Longo, Daniela; Palma, Paolo; et al. (Frontiers in Pediatrics, 2022)
Congenital cytomegalovirus (cCMV) infection can follow primary and secondary maternal infection. Growing evidence indicate that secondary maternal infections contribute to a much greater proportion of symptomatic cCMV than was previously thought. We performed a monocentric retrospective study of babies with cCMV evaluated from August 2004 to February 2021; we compared data of symptomatic children born to mothers with primary or secondary infection, both at birth and during long term follow up. Among the 145 babies with available data about maternal infection, 53 were classified as having symptomatic cCMV and were included in the study: 40 babies were born to mothers with primary infection and 13 babies were born to mothers with secondary infection. Analyzing data at birth, we found no statistical differences in the rate of clinical findings in the two groups, except for unilateral sensorineural hearing loss (SNHL) which was significantly more frequent in patients born to mother with secondary infection than in those born to mother with primary infection (46.2% vs 17.5%, P = 0.037). During follow up, we found a higher rate of many sequelae (tetraparesis, epilepsy, motor and speech delay, and unilateral SNHL) in the group of children born to mothers with secondary infection, with a statistical difference for tetraparesis and unilateral SNHL. Otherwise, only children born to mothers with primary infection presented bilateral SNHL both at birth and follow up. Our data suggest that the risk of symptomatic cCMV and long-term sequelae is similar in children born to mother with primary and secondary CMV infection; it is important to pay appropriate attention to seropositive mothers in order to prevent reinfection and to detect and possibly treat infected babies.